Lipoic Acid and Progesterone Alone or in Combination Ameliorate Retinal Degeneration in an Experimental Model of Hereditary Retinal Degeneration - Ramírez-Lamelas, Dolores T.; Benlloch-Navarro, Soledad; López-Pedrajas, Rosa; Gimeno-Hernández, Roberto; Olivar, Teresa; Silvestre, Dolores; Miranda, María (Frontiers in Pharmacology, 2018)
Retinitis pigmentosa (RP) is a group of inherited retinopathies characterized by photoreceptors death. Our group has shown the positive progesterone (P4) actions on cell death progression in an experimental model of RP. In an effort to enhance the beneficial effects of P4, the aim of this study was to combine P4 treatment with an antioxidant (lipoic acid [LA]) in the rd1 mice. rd1 and control mice were treated with 100 mg/kg body weight of P4, LA or a combination of both on postnatal day 7 (PN7), 9 and 11, and were sacrificed at PN11. The administration of LA and/or P4 diminishes cell death in rd1 retinas. The effect obtained after the combined administration of LA and P4 is higher than the one obtained with LA or P4 alone. The three treatments decreased GFAP staining, however, in the far peripheral retina, the two treatments that offered better results were LA and LA plus P4. LA or LA plus P4 increased retinal glutathione (GSH) concentration in the rd1 mice. Although LA and P4 are able to protect photoreceptors from death in rd1 mice retinas, a better effectiveness is achieved when administering LA and P4 at the same time.